Creative Writing for German Lessons in High School - Sobara, Iwa (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
Writing skills in a foreign language such as German are the most complicated skills compared to other language skills. When someone writes, they must pay attention to various aspects, namely: orthography, grammar, semantics, stylistics, pragmatic communication, and text patterns (Grimm et al., 2006: 23). According to previous studies, German teachers still have difficulties in teaching writing skill in senior high schools. In this article, we will describe creative writing training for German language learning in high school. The training participants were German teachers who are members of the Association of Indonesian German Language Teachers (Ikatan Guru Bahasa Jerman Indonesia/IGBJI) of Malang, East Java, with a total of 24 participants. The result of the training shows that German teachers in Malang got various interesting ideas for practicing writing skill in learning German. These ideas are Du hast nur 3 Wörter (You only have 3 words), Vergiss die Verben (forget the verbs), Der Superlativ (The superlative), Was wäre wenn… (What if), and Führe einen Blinden (Write for a blind person). The participants thought that they could apply these writing ideas in their learning activities in their classes.